2022
DOI: 10.3390/polym15010154
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanism of Bio-Based Sodium Alginate Fibers with Flame Retardant and Antibacterial Properties

Abstract: Flame retardant and antibacterial sodium alginate (SA) fiber were fabricated using the bio-based flame retardant of phytic acid and DL-arginine successively, and then the morphological structures, combustion behavior, thermal stability, and mechanical as well as antibacterial properties of SA fiber were investigated carefully. It is found that when the additional amount of PADL (reaction products of phytic acid and DL-arginine) in SA composite fiber is 20 wt%, its limiting oxygen index (LOI) is 40.0 ± 0.3%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…LC-MS data revealed that organic acids constituted 74.77% of the primary antibacterial components in the CFS of B. longum FB1-1. Notably, among the antibacterial substances detected, citric acid, epirizole, DL-arginine, and betaine exhibited higher relative abundances (as presented in Table 2 ) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC-MS data revealed that organic acids constituted 74.77% of the primary antibacterial components in the CFS of B. longum FB1-1. Notably, among the antibacterial substances detected, citric acid, epirizole, DL-arginine, and betaine exhibited higher relative abundances (as presented in Table 2 ) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…LC-MS data revealed that organic acids constituted 74.77% of the primary antibacterial components in the CFS of B. longum FB1-1. Notably, among the antibacterial substances detected, citric acid, epirizole, DL-arginine, and betaine exhibited higher relative abundances (as presented in Table 2) [25][26][27][28][29][30][31][32][33]. Figure 5A depicts experimental phenomena, showing that, although the inhibitory impact of high-temperature-treated CFS on CRKP was lower compared to the control, it still exhibited significant antibacterial activity, underscoring its potential as an antibacterial agent.…”
Section: Analysis Of Antibacterial Substancesmentioning
confidence: 96%
“…The presence of CO 2 (2362 and 669 cm −1 ) is readily discernible in the spectrum 40,41 . The presence of phosphorus‐based radicals, PO (1259 cm −1 ), can effectively quench energetic hydroxyl or hydrogen radicals generated during polymer decomposition in the gas phase, thereby interrupting flame propagation 42,43 …”
Section: Resultsmentioning
confidence: 99%